Implementasi Kebijakan Gerakan Literasi Sekolah dan Dampaknya terhadap Minat Baca Siswa pada Tingkat Sekolah Menengah atas Negeri di Kota Ternate - Silvani Umar Ali; Naniek Jusnita (Departement of Mathematics Education, 2023)
This study aims to know the facilitations, the implementation, and the impacts of school literacy program on students’ reading interest at Senior High School in Kota Ternate. This is qualitative research with descriptive analysis design. The subjects are the teachers and school principals at SMAN 1 Kota Ternate and SMAN 8 Kota Ternate. Data are gathered from interview, observation, and documentation. The results indicate that the literacy school program (GLS) has been implemented by the schools since 2016 when it was first launched by government. Schools facilitate books, chairs, and tables for reading corner, library, wall magazine. Reading corner is not only inside the classroom but also outside in school park. School also provides ‘Gazebos’, made from wood located in school park for students’ reading access. In practical situation, GLS is scheduled three (3) times then changed to five (5) times in a week. In two years, implementation, GLS has integrated in each school subject thus the student’s literacy competence has getting improved. Schools also implement fifteen (15) minutes of reading book before class. Students utilize their rest time or un-attendance teacher in class to spend their times in library or sit in reading corner. Another practical literacy accommodated in extracurricular activities are school competition, those are; create and read of poem, writing short story, writing essay, English speech, English debate. Through those literacy activity in both schools, students’ interest in reading has impacted positively on their daily school activity. Students are able to: 1) improve their understanding, 2) help improve their memory, 3) add knowledge and point of view, 4) improve vocabulary, 5) train their writing competence 6) improve their self-confidence, 7) improve communication skill.